Antifungal agents and the kidney: pharmacokinetics, clinical nephrotoxicity, and interactions. Issue 9 (2nd September 2021) - Tragiannidis, Athanasios; Gkampeta, Anastasia; Vousvouki, Maria; Vasileiou, Eleni; Groll, Andreas H.
ABSTRACT: Introduction: Invasive fungal infections continue to be important causes of morbidity and mortality in severely ill and immunocompromised patient populations. The past three decades have seen a considerable expansion in antifungal drug research, resulting in the clinical development of different classes of antifungal agents with different pharmacologic properties. Among drug-specific characteristics of antifungal agents, renal disposition and nephrotoxicity are important clinical considerations as many patients requiring antifungal therapy have compromised organ functions or are receiving other potentially nephrotoxic medications. Areas covered: The present article reviews incidence, severity and mechanisms of nephrotoxicity associated with antifungal agents used for prevention and treatment of invasive fungal diseases by discussing distribution, metabolism, elimination and drug-related adverse events in the context of safety data from phase II and III clinical studies. Expert opinion: Based on the available data amphotericin B deoxycholate has the highest relative potential for nephrotoxicity, followed by the lipid formulations of amphotericin B, and, to a much lesser extent and by indirect mechanisms, the antifungal triazoles.